REALISASI PRINSIP KERJASAMA DALAM SEBUAH INTERAKSI - -, M. Jazeri (Diksi, 2008)
This article describes the use and the violation of principles of cooperationor maxims. The maxims are used for some purposes. The maxim of quantity isused to express information clearly, to ask for help, and to avoid misunderstanding.The maxim of quality is used to express true information, to argue an opinion, andto make a conclusion. The maxim of relevance is used to find out true informationand to give true information. The maxim of manner is used to express informationclearly and to avoid misunderstanding.The violations of the maxims can be done by means of direct violation,opting out, clashing, and flouting. Such violations have some functions. Themaxim of quality is violated to raise a comic effect, to hide an intention, to flatter,and to hide embarrassment. The maxim of relevance is violated to raise aconversational implicature and to raise a comic effect. The maxim of manner isviolated to hide embarrassment, to raise a comic effect, and to raise aconversational implicature.Keywords: maxims of cooperation, maxim violation